The assessment of substances preferred by the cases, who applied to the adolescent addiction center, based on the [year]s - Yüncü, Z.; Bayram, A. T.; Altıntoprak, E.; Akgür, S. A.; Coşkunol, H.; Aydın, C.; Tamar, M. (Journal of Dependence, 2008)
Objective: Alcohol and substance use disorder (AUD) affects a significant segment of society. The first substance tried by individuals with AUD and the age at which they tried this substance vary from year to year. This study aimed to determine changes in some clinical characteristics (age of use, type of substance used, gender) among cases presenting to an addiction center where children and adolescents receive treatment. Method: The file records of cases presenting to an adolescent addiction center between September 2003 and September 2005 (dI) and September 2005 and September 2007 (dII) were scanned. The obtained information was analyzed using SPSS 11. Statistical significance was accepted as p
Keywords: dependence